Refugee Mental Health, Global Health Policy, and the Syrian Crisis - Cratsley, Kelso; Brooks, Mohamad Adam; Mackey, Tim K. (Frontiers in Public Health, 2021)
The most recent global refugee figures are staggering, with over 82.4 million people forcibly displaced and 26.4 million registered refugees. The ongoing conflict in Syria is a major contributor. After a decade of violence and destabilization, over 13.4 million Syrians have been displaced, including 6.7 million internally displaced persons and 6.7 million refugees registered in other countries. Beyond the immediate political and economic challenges, an essential component of any response to this humanitarian crisis must be health-related, including policies and interventions specific to mental health. This policy and practice review addresses refugee mental health in the context of the Syrian crisis, providing an update and overview of the current situation while exploring new initiatives in mental health research and global health policy that can help strengthen and expand services. Relevant global health policy frameworks are first briefly introduced, followed by a short summary of recent research on refugee mental health. We then provide an update on the current status of research, service provision, and health policy in the leading destinations for Syrians who have been forcibly displaced. This starts within Syria and then turns to Turkey, Lebanon, Jordan, and Germany. Finally, several general recommendations are discussed, including the pressing need for more data at each phase of migration, the expansion of integrated mental health services, and the explicit inclusion and prioritization of refugee mental health in national and global health policy.